Effect of chess teaching on mathematical, attention and concentration abilities in school-aged children of the Peruvian Amazon - Garate-Quispe, Jorge Santiago (2020)
The study aimed to analyze the influence of learning chess on mathematical, attention, and concentration abilities in school-aged children of two Schools in Peruvian Amazon. First-grade secondary school students were selected from two schools in Puerto Maldonado city, public and private. The design of the study was quasi-experimental, pretest-posttest evaluations and a control group. Each group had between 18-30 students, and the experimental group was given chess classes twice a week for three months. To analyze the effect of the intervention a Generalized Linear Model was used. In the two abilities evaluated, the posttest results of the experimental group were higher than the control group. A significant effect of the application of sports chess was found in the development of abilities in mathematical reasoning, attention, and concentration (P < 0.001). In the public school, the effect of the program on mathematical reasoning was higher in boys than in girls (P < 0.05). Our results provide relevant information for schools to develop strategies to promote chess as a teaching strategy. We concluded that the implementation of a chess program influences the development of the intellectual abilities in school-aged children of Peruvian Amazon.